Multidimensional risk of falls in elderly - Oliveira, Teresa (2018)
Objective: To identify the multidimensional risk factors for falls, present in a sample of elderly residents in the community. Methods: This is a descriptive, cross-sectional and exploratory study with a sample of 31 elderly people from a Community Care Unit in Lisbon and Tagus Valley Region, Portugal, between October 2016 and February 2017. Scales and instruments of functional evaluation were used in order to assess the risk factors. Descriptive statistics were used. Results: The majority of the sample is 75 years of age or older (67.7%, n=21) and presents more than one fall risk factor in each dimension. It is worth mentioning the walking speed decline, with 58.1% (n=16) of the elderly taking more than 12.6 seconds to perform the Timed Up and Go Test; 54.8% (n=17) being moderately or severely dependent; 48.3% (n=15) without or with little confidence in carrying out the activities; 38.7% (n=12) consumed benzodiazepines and an average of 4.6 medications per day. In the environmental evaluation of the home, researchers note that lighting is only adequate in kitchens. The totality of the elderly has at least one carpet at home; 38.7% (n=12) have one domestic animal inside the house and 61.3% (n=19) have at least one piece of unstable furniture. The safety behaviors are low: 98.6% (n=30) have never been alerted to the risks of falling, 61.3% (n=19) refer not to persevere in choosing the preventive measures. Conclusion: The risk factors for falls identified in the sample are multidimensional. Decreased gait velocity, poor confidence in performing the activities, polypharmacy and non-adoption of safety behaviors by the elderly stand out.